PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA DENGAN SISTEM PENGENDALIAN INTERNAL SEBAGAI VARIABEL INTERVENING (Studi Pada Desa di Kec.Tanah Luas Kabupaten Aceh Utara) - Aulia Aqmarina Sakdiah; Aiyub Aiyub; Adnan Adnan (J-MIND (Jurnal Manajemen Indonesia), 2022)
The purpose of this study is to empirically test and analyze the effect of village apparatus competence and the use of information technology on village fund management accountability through an internal control system. The respondents were 171 apparatus in Kecamatan Tanah Luas Kabupaten Aceh Utara Regencies taken using Census sampling. The analysis used was Structural Equation Modeling (SEM) with AMOS 21. The results of this study indicate that the competence of the village apparatus and the use of information technology have a positive effect on the accountability of village fund management. Meanwhile, the competence of the village apparatus and the use of information technology have a positive effect on the internal control system. The results show that the internal control system can mediate the competence of the village apparatus and the use of information technology on the accountability of village fund management in Kecamatan Tanah Luas Kabupaten Aceh Utara.